Innovation impact on organizational learning disabilities - Khaliq, Ahmad; Shalahudeen, Mohamed (Malaysian Institute of Management ( Institut Pengurusan Malaysia ), 2009)
Innovation and diffusion culture is key to the economic prosperity of a society. Learning disabilities do exist in some organizations due to a lack of innovativeness; nevertheless the diffusion of innovation to translate these innovations does play a significant role.This study explores the relationship between market culture and organizational learning disabilities in a leading marketing organization in a Muslim country.